Czech Republic : Enhancing the Prospects for Growth with Fiscal Stability - World Bank (Washington, DC: World Bank, 2013)
The Czech government is confronted with a worsening fiscal situation. The structural deficit ballooned in 2000, and it is expected to widen further in 2001. The report suggests that, at this stage of the recovery, fiscal retrenchment instead should be in order, both to make room for private demand to expand, without putting undue pressure on interest rates, and/or on the external current account, and, to set the country on track towards adhering to Stability and Growth Path when in the European Union (EU). The report sees a stronger case, and greater scope for adjustment on the expenditure, than on the revenue side. Expenditures have shot up in the last three years, to a level which exceeds those observed in comparable countries. Worse, most existing expenditure programs, seem locked in upward trajectories, and fresh spending pressures (arising from EU accession, contingent liabilities, or decentralization) are building up. The report illustrates, for selected sectors (bank restructuring, social protection, health, education, transport, and housing), the challenges involved in correcting expenditure trajectories. A key message is that, to succeed, the process of expenditure reform will need to be firmly grounded in the development of analytic capacities, in both core and line agencies, linked with enhancements in the country's institutions, and procedures for fiscal management.